(untitled) (Research, Society and Development, 2022)
The objective of this study is to explain the importance of satellite pharmacy in the emergency sector, both for professionals and in the care and care of critically ill patients, reporting how the multidisciplinary team positions itself on the topic to be debated. Also clarify the difficulty of acquiring a pharmacy in the sector, the issue of resources, funds, hiring employees (pharmacists, assistants, interns, etc.). This writing will be carried out through exploratory and qualitative research with the application of a questionnaire prepared on the Google forms platform, the participants will be professionals from the nursing staff who work in hospitals., The data will be analyzed and described according to the answers, according to the researched theoretical framework. Among the results, we sought to list the needs and challenges encountered by health professionals who work in services that do not have satellite pharmacy, pointing out the consequences arising from this shortage, highlighting the importance of a logistical adjustment in the dispensing of medicines, to ensure speed and safety for patients seeking emergency service.